Deadstream [videorecording (DVD)] - Winter, Vanessa (Filmmaker); Winter, Joseph; Winter, Joseph; Winter, Joseph; Stone, Melanie (Shudder, 2023)
A disgraced internet personality attempts to win back his followers by live-streaming one night alone in a haunted house. But when he accidentally pisses off a vengeful spirit, his big comeback event quickly becomes a real-life fight for his life.